2013
DOI: 10.4338/aci-2013-05-ra-0033
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Derivation and Validation of a Search Algorithm to Identify Emergent Endotracheal Intubations in the Intensive Care Unit

Abstract: KeywordsElectronic medical record, emergent, endotracheal intubation, intensive care unit, search algorithm SummaryBackground: The development and validation of automated electronic medical record (EMR) search strategies are important in identifying emergent endotracheal intubations in the intensive care unit (ICU). Objective: To develop and validate an automated search algorithm (strategy) for emergent endotracheal intubation in the critically ill patient. Methods: The EMR search algorithm was created through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Comparison of the two methodologies demonstrated that the sensitivity and specificity of the automated search algorithm could approach 100% in many instances. These findings further corroborate previously published studies demonstrating that the use of automated search strategies produced very accurate results that were agreeable with those produced by manual review and data extraction methods [2,4,6,7]. Additionally, this study demonstrates that this methodology can be a reliable alternative to manual chart review for research pertaining to postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Comparison of the two methodologies demonstrated that the sensitivity and specificity of the automated search algorithm could approach 100% in many instances. These findings further corroborate previously published studies demonstrating that the use of automated search strategies produced very accurate results that were agreeable with those produced by manual review and data extraction methods [2,4,6,7]. Additionally, this study demonstrates that this methodology can be a reliable alternative to manual chart review for research pertaining to postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
“…A commercially available, web-based query-building tool called Data Discovery and Query Builder (DDQB) was utilized for interrogation of data files contained within the databases listed above (International Business Machines, Corp). The DDQB tool allows clinicians and researchers without extensive programming knowledge to build complex queries based on Boolean logic and free-text searches [4,6]. These tools were used to search through patient records in the EMR to identify deep venous thrombosis, pulmonary embolism, or myocardial infarction within 30 days of the lower extremity orthopedic procedure.…”
Section: Automated Electronic Data Extraction Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, automated search strategies have been used to identify certain elements in a patient’s EMR [6,7]. Recently, Smischney et al [7] developed and validated automated electronic search strategies to identify emergent intubations from EMRs.…”
Section: Introductionmentioning
confidence: 99%
“…Our results add credence to the use of computerized searches of EHRs of large patient cohorts to extract clinical variables, processes, and outcomes of interest. (2,3,(12)(13)(14) The increased perioperative risk that OSA poses for surgical patients is well recognized, (4,5) and the condition has become the topic of clinical management guidelines that call for increased vigilance of affected patients. (11,15) Despite the risk, OSA may present with vague symptoms (eg, increased daytime sleepiness), and population studies have suggested that most (approximately 90%) of OSA cases are undiagnosed, (7) including OSA of surgical patients.…”
Section: Discussionmentioning
confidence: 99%